Lightweight thermal insulation and sound insulation mortar and preparation method thereof

By adding thermal insulation ceramic microbeads and polymer damping materials to the mortar, the problem of insufficient thermal insulation performance of mortar in the prior art is solved, and the excellent sound insulation, thermal insulation performance and compressive strength of the mortar are achieved.

CN119613146AInactive Publication Date: 2025-03-14YANCHENG FUBANG NEW BUILDING MATERIALS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411680360.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, there is no composition of modified drift beads or rubber to further improve the thermal insulation performance of the mortar.

Method used

The lightweight insulation and sound insulation mortar is prepared by adding components such as sulfur-aluminate cement, silicate cement, hollow glass microbeads, reinforced fibers, polymer damping materials, fly ash, fine sand, latex powder, water reducing agent and dispersant.

Benefits of technology

It significantly improves the sound insulation and heat insulation properties of the mortar, and has good compressive strength and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005148179950000111
    Figure BDA0005148179950000111
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and particularly relates to lightweight thermal insulation and sound insulation mortar and a preparation method thereof. The hollow ceramic microbeads are used as a carrier, and the undecanoic acid-solid paraffin binary phase change material is added, so that the prepared thermal insulation ceramic microbeads have excellent thermal insulation performance and certain self-adaptive temperature change capability; the high-molecular damping material prepared by filling mica sheets co-modified by stearic acid and a silane coupling agent with methyl vinyl silicone rubber as a carrier has excellent sound insulation performance, and can improve the mechanical property of mortar and reduce the cracking phenomenon of the mortar by blending with fibers. The lightweight thermal insulation mortar prepared by adding the thermal insulation ceramic microbeads and the polymer damping material on the basis of the existing components has excellent sound insulation and thermal insulation performance, and has relatively good compressive strength and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to a lightweight thermal insulation and sound insulation mortar and a preparation method thereof. Background Art

[0002] With the development of urbanization, people's living standards have been greatly improved, and people's requirements for residential insulation and sound insulation are increasing. The quality of residential sound insulation not only affects people's living comfort, but also affects people's physical and mental health. In order to maintain a stable indoor temperature, people need to use cooling and heating equipment to consume energy to adjust the indoor temperature. In order to achieve energy saving and consumption reduction, it is necessary to reduce the use time of cooling and heating equipment. Therefore, it is an important measure to achieve building energy saving by insulating the walls. Traditional buildings use untreated reinforced cement concrete slabs with poor sound insulation and thermal insulation performance. Polyurethane boards are usually used as thermal insulation materials, and sound insulation materials are usually sound insulation cotton. However, polyurethane boards are only used as thermal insulation materials and cannot achieve functions such as energy storage and temperature regulation. Sound insulation cotton needs to be installed outside the building wall, which is not only expensive but also increases the difficulty of construction.

[0003] Patent CN115611583B discloses a thermal insulation and sound insulation mortar and its preparation method and application. It includes the following components calculated by weight: 150-260 parts of cement; 20-50 parts of floating beads; 50-100 parts of rubber powder; 4.5-15 parts of polystyrene foam particles; 60-150 parts of light sand; 1-3 parts of redispersible latex powder; 1-1.5 parts of hydroxypropyl methylcellulose ether; 1-1.5 parts of short-cut polypropylene fiber. The patent selects floating beads, rubber powder, polystyrene foam particles and redispersible latex powder as mortar components, so that the mortar not only has the effect of thermal insulation and sound insulation, but also has good compressive strength. However, the prior art still has the technical problem of not further improving the thermal insulation and sound insulation performance of the mortar by modifying the composition of floating beads or rubber. Summary of the invention

[0004] The object of the present invention is to provide a lightweight thermal insulation and sound insulation mortar and a preparation method thereof, so as to solve the technical problem in the prior art that the thermal insulation and sound insulation performance of the mortar cannot be further improved by modifying the composition of floating beads or rubber.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A thermal insulation and sound insulation mortar is prepared from the following components in parts by weight:

[0007] 5-20 parts of sulphoaluminate cement, 80-100 parts of silicate cement, 10-20 parts of thermal insulation ceramic microspheres, 5-20 parts of hollow glass microspheres, 0.5-2 parts of reinforcing fibers, 10-30 parts of polymer damping materials, 15-25 parts of fly ash, 100-150 parts of fine sand, 5-10 parts of latex powder, 0.5-3 parts of water reducer, 0.5-3 parts of dispersant, and 50-100 parts of water.

[0008] Preferably, the thermal insulation ceramic microbeads are hollow ceramic microbeads that adsorb undecanoic acid / solid paraffin binary phase change material.

[0009] Preferably, the particle size of the hollow glass microspheres is 20 to 40 μm.

[0010] Preferably, the reinforcing fiber is a combination of one or more of polypropylene fiber, polyvinyl alcohol fiber and carbon fiber.

[0011] Preferably, the polymer damping material is methyl vinyl silicone rubber filled with modified mica sheets.

[0012] Preferably, the fly ash is Class I fly ash.

[0013] Preferably, the latex powder is one or both of ethylene-vinyl acetate copolymer and vinyl acetate-versatate copolymer.

[0014] Preferably, the water reducer is a polycarboxylic acid water reducer.

[0015] Preferably, the dispersant is a combination of one or more of sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose and sodium lignin sulfonate.

[0016] The preparation method of the lightweight thermal insulation and sound insulation mortar comprises the following steps:

[0017] S1. Add sulphoaluminate cement, silicate cement, thermal insulation ceramic microspheres, glass microspheres, fibers, fly ash and fine sand into a mixer and stir;

[0018] S2. Add water, latex powder, water reducing agent and dispersant into a mixer and stir slowly and then quickly. After stopping stirring, pour into a mold and vibrate;

[0019] S3, placing the mold in a standard curing room for curing for 1 to 2 days, and then demoulding to obtain a lightweight thermal insulation and sound insulation mortar. As a further improved solution of the present invention, the preparation method of thermal insulation ceramic microspheres includes the following steps:

[0020] S11, adding undecanoic acid and solid paraffin into a container, heating in a water bath until they are molten and stirring continuously, and cooling naturally to obtain an undecanoic acid / solid paraffin binary phase change material;

[0021] S12, adding undecanoic acid / solid paraffin binary phase change material and hollow ceramic microbeads into a container, heating in a water bath with continuous stirring, and naturally cooling after adsorption to obtain a composite system of undecanoic acid / solid paraffin binary phase change material and ceramic microbeads;

[0022] S13, after uniformly mixing the composite system of undecanoic acid / solid paraffin binary phase change material and hollow ceramic microspheres and the packaging material, spreading them on a flat surface, and preparing thermal insulation ceramic microspheres after natural drying.

[0023] Preferably, the melting point of the solid paraffin in S11 is 47-51° C., and the mass ratio of undecanoic acid to the solid paraffin is 7-8:2-3.

[0024] Preferably, the water bath heating temperature in S11 is 70-80° C., and the stirring time is 5-10 min.

[0025] Preferably, the S12 hollow ceramic microbeads are composed of silicon dioxide and aluminum oxide, and have a particle size of 50 to 100 μm.

[0026] Preferably, the mass ratio of the undecanoic acid / solid paraffin binary phase change material and the hollow ceramic microbeads in the S12 is 2 to 2.5:1.

[0027] Preferably, the water bath heating temperature in S12 is 45-60° C., and the adsorption time is 60-90 min.

[0028] Preferably, the packaging material in S13 is epoxy resin-polyurethane-Silicate cement, and the mass ratio of epoxy resin, polyurethane and Silicate cement is 1:1:2-3.

[0029] As a further improved solution of the present invention, a method for preparing a polymer damping material comprises the following steps:

[0030] S21, adding methyl vinyl silicone rubber into an internal mixer, adding modified mica flakes three times, and mixing until the modified mica flakes are completely mixed into the methyl vinyl silicone rubber;

[0031] S22, re-refining until the modified mica sheet and the methyl vinyl silicone rubber are uniformly mixed, and then leaving at room temperature for 1 week to obtain a silicone rubber mixture;

[0032] S23, putting the silicone rubber mixture into an open mill and mixing it until it is completely rolled, adding a vulcanizing agent at room temperature and passing it thinly on the open mill, and removing it after mixing evenly to obtain a mixed rubber;

[0033] S24, the mixed rubber is put into a mold, vulcanized and formed on a flat vulcanizer, and granulated to obtain a granular polymer damping material.

[0034] The method for preparing the modified mica sheet comprises the following steps:

[0035] S31, adding a silane coupling agent dropwise into a mixed liquid of deionized water and anhydrous ethanol to react to obtain a modified liquid;

[0036] S32, placing the nano-mica sheet in an oven and baking it to obtain an active mica sheet;

[0037] S33, adding active mica flakes and stearic acid to the modified liquid, adjusting the pH to 4-5 with acetic acid, stirring and dispersing the mixture evenly, and reacting the mixture at room temperature;

[0038] S34. After the reaction is completed, the reaction liquid is placed in an oven for drying to obtain a modified mica sheet.

[0039] Preferably, the mass ratio of methyl vinyl silicone rubber to modified mica sheet in S21 is 99.2-99.7:0.3-0.8.

[0040] Preferably, the mixing temperature in S21 is 60-70° C., the mixing interval is 5 minutes, and the single mixing time is 10-15 minutes.

[0041] Preferably, the back-refining temperature in S22 is 70-75° C., and the back-refining time is 10-20 min.

[0042] Preferably, the vulcanizing agent in S23 is any one of benzoyl peroxide, 2,4-dichlorobenzoyl peroxide, and diisopropylbenzene peroxide.

[0043] Preferably, in S24, the vulcanizing agent is benzoyl peroxide, the vulcanizing temperature is 110-130°C, and the vulcanizing time is 30-40 min; the vulcanizing agent is 2,4-dichlorobenzoyl peroxide, the vulcanizing temperature is 100-120°C, and the vulcanizing time is 30-40 min; the vulcanizing agent is diisopropylbenzene peroxide, the vulcanizing temperature is 150-160°C, and the vulcanizing time is 30-40 min.

[0044] Preferably, the silane coupling agent in S31 is any one of KH-550, KH-560 and KH-570.

[0045] Preferably, the mass ratio of the silane coupling agent, deionized water and anhydrous ethanol in S31 is 1:1:18-25, and the reaction is carried out at room temperature for 30-40 minutes.

[0046] Preferably, the oven temperature in S32 is set to 100-120° C., and the baking time is 1-2 hours.

[0047] Preferably, the ratio of active mica flakes, stearic acid and modified liquid in S33 is 1-2:2-4:50.

[0048] Preferably, in S33, the stirring speed is 1000-2000 rpm, the stirring time is 30-40 min, and the reaction is carried out at room temperature for 2-4 h after the stirring is completed.

[0049] Preferably, in S34, the oven temperature is set to 120-130° C., and the baking time is 2-3 hours.

[0050] Preferably, the stirring speed of the stirrer in S1 is set to 80-130 rpm, and the stirring time is 3-5 min.

[0051] Preferably, in S2, the slow stirring is 80-130 rpm, the stirring time is 2-3 min, and the fast stirring is 150-200 rpm, the stirring time is 2-3 min.

[0052] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0053] 1. The lightweight thermal insulation mortar prepared by the present invention by adding thermal insulation ceramic microspheres and polymer damping materials to the existing components has excellent sound insulation and heat insulation properties, and has good compressive strength and corrosion resistance.

[0054] 2. The thermal insulation ceramic microspheres made by using hollow ceramic microspheres as carriers and adding undecanoic acid / solid paraffin binary phase change materials have excellent thermal insulation properties, and can automatically store or release heat in response to changes in ambient temperature, and have a certain adaptive temperature change capability.

[0055] 3. The polymer damping material made of mica sheets modified by stearic acid and silane coupling agent filled with methyl vinyl silicone rubber as a carrier has excellent sound insulation performance, and blending with fibers can improve the mechanical properties of mortar, reduce mortar cracking, and make the mortar anti-corrosion.

[0056] 4. Compared with single silicate cement, sulphoaluminate cement and silicate cement are used as cementitious materials, which makes the mortar have better adhesion, smaller drying shrinkage, certain early strength and corrosion resistance. DETAILED DESCRIPTION

[0057] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0058] Example 1: A thermal insulation and sound insulation mortar of this example is prepared from the following components in parts by weight:

[0059] 15 parts of sulphoaluminate cement, 85 parts of silicate cement, 10 parts of thermal insulation ceramic microspheres, 20 parts of hollow glass microspheres, 2 parts of reinforcing fibers, 10 parts of polymer damping materials, 15 parts of fly ash, 70 parts of fine sand, 5 parts of latex powder, 0.5 parts of water reducer, 0.5 parts of dispersant, and 60 parts of water. The particle size of the hollow glass microspheres is 20 μm, the reinforcing fibers are polypropylene fibers, the fly ash is Class I fly ash, the latex powder is ethylene-vinyl acetate copolymer, the water reducer is a polycarboxylic acid high-performance water reducer with a solid content of 40% produced by Hangzhou Shibao Company, and the dispersant is sodium carboxymethyl cellulose.

[0060] The preparation method of the lightweight thermal insulation and sound insulation mortar comprises the following steps:

[0061] S1. Add the above-mentioned portions of sulphoaluminate cement, silicate cement, thermal insulation ceramic microspheres, glass microspheres, fibers, fly ash and fine sand into a mixer, set the mixer speed to 80 rpm, and stir for 3 min;

[0062] S2, add water, latex powder, water reducing agent and dispersant into the mixer, stir slowly and then quickly, the slow stirring is 80rpm, the stirring time is 2min, the fast stirring is 150rpm, the stirring time is 2min, stop stirring and pour into the mold for casting and vibration;

[0063] S3. Place the mold in a standard curing room and cure for 1 day before demoulding to obtain a lightweight thermal insulation and sound insulation mortar.

[0064] The preparation method of thermal insulation ceramic microspheres comprises the following steps:

[0065] S11, adding 7 parts of undecanoic acid and 3 parts of solid paraffin into a container, heating in a water bath at 70° C., stirring for 5 min, and cooling naturally to obtain an undecanoic acid / solid paraffin binary phase change material;

[0066] S12, adding 10 parts of undecanoic acid / solid paraffin binary phase change material and 5 parts of hollow ceramic microspheres with a particle size of 50 μm into a container, heating in a water bath with continuous stirring, the water bath heating temperature is 45° C., the adsorption time is 60 min, and after the adsorption is completed, naturally cooling is performed to obtain a composite system of undecanoic acid / solid paraffin binary phase change material and ceramic microspheres;

[0067] S13. Evenly mix 15 parts of a composite system of undecanoic acid / solid paraffin binary phase change material and hollow ceramic microspheres and a packaging material of 1 part of epoxy resin, 1 part of polyurethane and 2 parts of silicate cement, spread them on a flat surface, and dry them naturally to obtain thermal insulation ceramic microspheres.

[0068] The preparation method of the polymer damping material comprises the following steps:

[0069] S21, adding methyl vinyl silicone rubber into an internal mixer, adding modified mica flakes in three times, the mixing temperature is 70° C., the mixing interval is 5 minutes, the single mixing time is 10 minutes, and the mixing is continued until the modified mica flakes are completely mixed into the methyl vinyl silicone rubber;

[0070] S22, re-mixing at 70°C for 10 minutes until the modified mica sheet and the methyl vinyl silicone rubber are uniformly mixed, and then leaving at room temperature for 1 week to obtain a silicone rubber mixture;

[0071] S23, putting the silicone rubber mixture into an open mill and mixing it until it is completely rolled, adding benzoyl peroxide at room temperature and passing it thinly on the open mill, and removing it after mixing evenly to obtain a mixed rubber;

[0072] S24. The mixed rubber is placed in a mold and vulcanized on a flat vulcanizer at 110° C. for 30 minutes to obtain a granular polymer damping material.

[0073] The method for preparing the modified mica sheet comprises the following steps:

[0074] S31, adding 3 parts of silane coupling agent dropwise to a mixed liquid of 3 parts of deionized water and 54 parts of anhydrous ethanol, and reacting at room temperature for 30 minutes to obtain a modified liquid;

[0075] S32, placing the nano-mica sheet in an oven, and baking at 100° C. for 1 h to obtain an active mica sheet;

[0076] S33, adding 1 part of active mica flakes and 2 parts of stearic acid to 50 parts of modified liquid, adjusting the pH to 4 with acetic acid, setting the stirring speed to 1000 rpm, stirring time to 30 min, stirring and dispersing evenly, and reacting at room temperature for 2 h;

[0077] S34. After the reaction is completed, the reaction liquid is placed in an oven and dried at 120° C. for 2 hours to obtain a modified mica sheet.

[0078] Example 2: A thermal insulation and sound insulation mortar of this example is prepared from the following components in parts by weight:

[0079] 10 parts of sulphoaluminate cement, 90 parts of silicate cement, 20 parts of thermal insulation ceramic microspheres, 15 parts of hollow glass microspheres, 1 part of reinforcing fiber, 20 parts of polymer damping material, 20 parts of fly ash, 80 parts of fine sand, 8 parts of latex powder, 1 part of water reducer, 1 part of dispersant, and 90 parts of water. The particle size of the hollow glass microspheres is 20 μm, the reinforcing fiber is polyvinyl alcohol fiber, the fly ash is Class I fly ash, the latex powder is ethylene-vinyl acetate copolymer, the water reducer is a polycarboxylic acid high-performance water reducer with a solid content of 40% produced by Hangzhou Shibao Company, and the dispersant is sodium carboxymethyl cellulose.

[0080] The preparation method of the lightweight thermal insulation and sound insulation mortar comprises the following steps:

[0081] S1. Add the above-mentioned portions of sulphoaluminate cement, silicate cement, thermal insulation ceramic microspheres, glass microspheres, fibers, fly ash and fine sand into a mixer, set the mixer speed to 100 rpm, and stir for 3 min;

[0082] S2, add water, latex powder, water reducing agent and dispersant into the mixer, stir slowly and then quickly, the slow stirring is 100 rpm, the stirring time is 2 min, the fast stirring is 150 rpm, the stirring time is 3 min, stop stirring and pour into the mold for casting and vibration;

[0083] S3. Place the mold in a standard curing room and cure for 1 day before demoulding to obtain a lightweight thermal insulation and sound insulation mortar.

[0084] The difference between the thermal insulation ceramic microspheres and Example 1 is that the material components in the binary phase change material are 8 parts of undecanoic acid and 2 parts of solid paraffin, and the particle size of the hollow ceramic microspheres is 70 μm.

[0085] The difference between the polymer damping material and Example 1 is that the vulcanizing agent is 2,4-dichlorobenzoyl peroxide, the vulcanization temperature is 110° C., and the vulcanization time is 35 min.

[0086] Example 3: A thermal insulation and sound insulation mortar of this example is prepared from the following components in parts by weight:

[0087] 20 parts of sulphoaluminate cement, 80 parts of silicate cement, 30 parts of thermal insulation ceramic microspheres, 5 parts of hollow glass microspheres, 0.5 parts of reinforcing fibers, 30 parts of polymer damping materials, 25 parts of fly ash, 100 parts of fine sand, 10 parts of latex powder, 3 parts of water reducer, 3 parts of dispersant, and 100 parts of water. The hollow glass microspheres have a particle size of 40 μm, the reinforcing fibers are polyvinyl alcohol fibers, the fly ash is Class I fly ash, the latex powder is vinyl acetate-versatate copolymer, the water reducer is a polycarboxylic acid high-performance water reducer with a solid content of 40% produced by Hangzhou Shibao Company, and the dispersant is hydroxypropyl methylcellulose.

[0088] The preparation method of the lightweight thermal insulation and sound insulation mortar comprises the following steps:

[0089] S1. Add the above-mentioned portions of sulphoaluminate cement, silicate cement, thermal insulation ceramic microspheres, glass microspheres, fiber, fly ash and fine sand into a mixer, set the mixer speed to 130 rpm, and stir for 3 min;

[0090] S2, add water, latex powder, water reducing agent and dispersant into the mixer, stir slowly and then quickly, the slow stirring is 130rpm, the stirring time is 2min, the fast stirring is 200rpm, the stirring time is 3min, stop stirring and pour into the mold for casting and vibration;

[0091] S3. Place the mold in a standard curing room and cure for 2 days before demoulding to obtain a lightweight thermal insulation and sound insulation mortar.

[0092] The difference between the thermal insulation ceramic microspheres and Example 1 is that the material components in the binary phase change material are 7.5 parts of undecanoic acid and 2.5 parts of solid paraffin, and the particle size of the hollow ceramic microspheres is 100 μm.

[0093] The difference between the polymer damping material and Example 1 is that the vulcanizing agent is dicumyl peroxide, the vulcanization temperature is 160° C., and the vulcanization time is 40 min.

[0094] Example 4: A thermal insulation and sound insulation mortar of this example is prepared from the following components in parts by weight:

[0095] 12 parts of sulphoaluminate cement, 88 parts of silicate cement, 30 parts of thermal insulation ceramic microspheres, 20 parts of hollow glass microspheres, 2 parts of reinforcing fibers, 20 parts of polymer damping materials, 20 parts of fly ash, 100 parts of fine sand, 10 parts of latex powder, 3 parts of water reducer, 3 parts of dispersant, and 100 parts of water. The hollow glass microspheres have a particle size of 20 μm, the reinforcing fibers are polyvinyl alcohol fibers, the fly ash is Class I fly ash, the latex powder is vinyl acetate-versatate copolymer, the water reducer is a polycarboxylic acid high-performance water reducer with a solid content of 40% produced by Hangzhou Shibao Company, and the dispersant is hydroxypropyl methylcellulose.

[0096] The preparation method of the lightweight thermal insulation and sound insulation mortar comprises the following steps:

[0097] S1. Add the above-mentioned portions of sulphoaluminate cement, silicate cement, thermal insulation ceramic microspheres, glass microspheres, fibers, fly ash and fine sand into a mixer, set the mixer speed to 100 rpm, and stir for 3 min;

[0098] S2, add water, latex powder, water reducing agent and dispersant into the mixer, stir slowly and then quickly, the slow stirring is 100 rpm, the stirring time is 2 min, the fast stirring is 200 rpm, the stirring time is 3 min, stop stirring and pour into the mold for casting and vibration;

[0099] S3. Place the mold in a standard curing room and cure for 1 day before demoulding to obtain a lightweight thermal insulation and sound insulation mortar.

[0100] The difference between the thermal insulation ceramic microspheres and Example 1 is that the material components in the binary phase change material are 8 parts of undecanoic acid and 3 parts of solid paraffin, and the particle size of the hollow ceramic microspheres is 80 μm.

[0101] The polymer damping material is the same as that used in Example 3.

[0102] Comparative Example 1: The difference between this comparative example and Example 1 is that the thermal insulation ceramic microspheres and hollow glass microspheres are replaced by expanded perlite.

[0103] Comparative Example 2: This comparative example differs from Example 1 in that the polymer damping material is replaced by EPDM rubber particles.

[0104] Test Case

[0105] Dry density test

[0106] The thermal insulation and sound insulation mortar was made into 5 pieces of 300mm×300mm×30mm test pieces and placed in a drying oven for drying. After measuring the volume and mass of the test pieces, the density was calculated and the average value was taken. The calculation formula is as follows:

[0107]

[0108] ρ is the specimen density, in kg / m 3 ;

[0109] M is the mass of the specimen, in kg;

[0110] V is the volume of the specimen, in m 3 .

[0111] The test results are shown in Table 1 below:

[0112] Table 1

[0113] Serial number <![CDATA[Dry density (kg / m 3 )]]> Example 1 441 Example 2 469 Example 3 485 Example 4 470 Comparative Example 1 421 Comparative Example 2 444

[0114] Mechanical properties test

[0115] The mechanical properties test was carried out in accordance with GB / T 20473-2006 "Building Thermal Insulation Mortar", and the compressive strength after curing for 28 days and the tensile bond strength after curing for 28 days were tested. The test results are shown in Table 2 below:

[0116] Table 2

[0117] Serial number 28d compressive strength (MPa) 28d tensile bond strength (MPa) Example 1 1.21 0.64 Example 2 1.34 0.68 Example 3 1.47 0.63 Example 4 1.55 0.61 Comparative Example 1 1.03 0.56 Comparative Example 2 0.96 0.52

[0118] Thermal performance test

[0119] The thermal conductivity of each embodiment and comparative example after curing for 28 days was measured with reference to the standard GB / T 10297-2015 "Hot wire method for determination of thermal conductivity of non-metallic solid materials", and the specific heat capacity of each embodiment and comparative example was tested by a thermal constant analyzer. The test results are shown in Table 3 below:

[0120] Table 3

[0121] Serial number Thermal conductivity (w / m·k) Specific heat capacity (kJ / (kg·K)) Example 1 0.071 0.84 Example 2 0.067 0.91 Example 3 0.065 0.97 Example 4 0.062 0.95 Comparative Example 1 0.081 0.59 Comparative Example 2 0.070 0.81

[0122] Sound insulation performance test

[0123] Reference standards GB50118-2010 "Civil Building Sound Insulation Design Code" and GB / T 19889.8-2006 "Acoustic Building and Building Component Sound Insulation Measurement Part 8: Laboratory Measurement of Impact Sound Improvement of Heavy Standard Floor Covering" were used to establish a reference floor slab, the thickness of which was 120 mm, of which 30 mm of mortar was applied on each side, and the weighted impact sound pressure level of the hollow block when the sound insulation mortar was not applied was 81 dB, and the weighted impact sound pressure levels of each embodiment and comparative example were measured. The test results are shown in Table 4 below:

[0124] Table 4

[0125] Serial number Weighted impact sound pressure level (dB) Example 1 65 Example 2 63 Example 3 61 Example 4 63 Comparative Example 1 69 Comparative Example 2 76

[0126] It can be seen from the data in Tables 1 to 4 that the dry density of Examples 1 to 4 is all above 500 kg / m 3 The results show that the mortar prepared by the present invention has excellent mechanical properties and meets the mechanical properties requirements of building thermal insulation mortar; the thermal conductivity coefficient after 28 days of curing is below 0.08w / m·k, and the specific heat capacity is above 0.8kJ / (kg·K), which shows that the mortar prepared by the present invention is an excellent thermal insulation material with good heat storage performance, and the weighted impact sound pressure level is 65dB or below, which shows that the mortar prepared by the present invention has excellent sound insulation performance and meets the requirements of the current civil building sound insulation standards. It is further explained that the mortar prepared by the present invention is a high-performance lightweight thermal insulation and sound insulation mortar.

[0127] The dry density of Comparative Example 1 is lower than that of each embodiment, the compressive strength after curing for 28 days is 1.03 MPa, the tensile bond strength after curing for 28 days is 0.56 MPa, the thermal conductivity after curing for 28 days is above 0.12 w / m·k, the specific heat capacity is less than 0.6 kJ / (kg·K), and the weighted impact sound pressure level is greater than 65 dB, indicating that after the thermal insulation ceramic microspheres and hollow glass microspheres are replaced with expanded perlite with a smaller dry density, although the dry density of the mortar is smaller, the mechanical properties are lower than those of the embodiments after long-term curing, the thermal insulation capacity is reduced and the specific heat capacity is low, indicating that the thermal insulation performance of the expanded perlite cannot be stably maintained in the later stage, and its toughening and strengthening capabilities are not as good as those of the composite use of thermal insulation ceramic microspheres and hollow glass microspheres, and it does not have excellent heat storage capacity. It further illustrates that the composite use of thermal insulation ceramic microspheres and hollow glass microspheres can improve the mechanical properties and sound insulation effects of the mortar within a certain range.

[0128] The compressive strength of Comparative Example 2 after 28 days of curing is 0.96 MPa, the tensile bond strength after 28 days of curing is 0.52 MPa, and the weighted impact sound pressure level is greater than 75 dB, indicating that the mechanical properties of the mortar with the addition of polymer damping material are better than those of the mortar with the addition of EPDM rubber particles, and the sound insulation effect of the polymer damping material is better than that of the EPDM rubber particles, further illustrating that the polymer damping material has excellent toughening, strengthening and sound insulation capabilities, and the mortar with the addition of polymer damping material can improve the mechanical properties and sound insulation effects of the mortar.

[0129] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0130] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A thermal insulation and sound insulation mortar, characterized in that: It is prepared from the following ingredients in parts by weight: 5-20 parts of sulphoaluminate cement, 80-100 parts of silicate cement, 10-30 parts of thermal insulation ceramic microspheres, 5-20 parts of hollow glass microspheres, 0.5-2 parts of reinforcing fiber, 10-30 parts of polymer damping material, 15-25 parts of fly ash, 70-100 parts of fine sand, 5-10 parts of latex powder, 0.5-3 parts of water reducer, 0.5-3 parts of dispersant and 50-100 parts of water. The thermal insulation ceramic microspheres are hollow ceramic microspheres that absorb undecanoic acid / solid paraffin binary phase change material, and the polymer damping material is methyl vinyl silicone rubber filled with modified mica sheets.

2. The thermal insulation and sound insulation mortar according to claim 1, characterized in that: The particle size of the hollow glass microspheres is 20 to 40 μm, the reinforcing fibers are a combination of one or more of polypropylene fibers, polyvinyl alcohol fibers and carbon fibers, the polymer damping material is methyl vinyl silicone rubber filled with modified mica sheets, the fly ash is Class I fly ash, the latex powder is one or two of ethylene-vinyl acetate copolymer and vinyl acetate-versatate copolymer, the water reducer is a polycarboxylic acid water reducer, and the dispersant is a combination of one or more of sodium carboxymethyl cellulose, hydroxypropyl methylcellulose and sodium lignin sulfonate.

3. A method for preparing a thermal insulation and sound insulation mortar, characterized in that: The steps include: S1. Add sulphoaluminate cement, silicate cement, thermal insulation ceramic microspheres, glass microspheres, fibers, fly ash and fine sand into a mixer and stir; S2. Add water, latex powder, water reducing agent and dispersant into a mixer and stir slowly and then quickly. After stopping stirring, pour into a mold and vibrate; S3. Place the mold in a standard curing room and cure for 1 to 2 days before demoulding to obtain a lightweight thermal insulation and sound insulation mortar.

4. The method for preparing a thermal insulation and sound insulation mortar according to claim 3, characterized in that: The preparation method of thermal insulation ceramic microspheres comprises the following steps: S11, adding undecanoic acid and solid paraffin into a container, heating in a water bath until they are molten and stirring continuously, and cooling naturally to obtain an undecanoic acid / solid paraffin binary phase change material; S12, adding undecanoic acid / solid paraffin binary phase change material and hollow ceramic microbeads into a container, heating in a water bath with continuous stirring, and naturally cooling after adsorption to obtain a composite system of undecanoic acid / solid paraffin binary phase change material and ceramic microbeads; S13, after uniformly mixing the composite system of undecanoic acid / solid paraffin binary phase change material and hollow ceramic microspheres and the packaging material, spreading them on a flat surface, and preparing thermal insulation ceramic microspheres after natural drying.

5. The method for preparing a thermal insulation and sound insulation mortar according to claim 4, characterized in that: The melting point of the solid paraffin in the S11 is 47-51°C, the mass ratio of undecanoic acid to solid paraffin is 7-8:2-3, the water bath heating temperature is 70-80°C, and the stirring time is 5-10 min. The hollow ceramic microbeads in the S12 are composed of silicon dioxide and aluminum oxide, with a particle size of 50-100 μm, the mass ratio of undecanoic acid / solid paraffin binary phase change material and hollow ceramic microbeads is 2-2.5:1, the water bath heating temperature is 45-60°C, and the adsorption time is 60-90 min. The packaging material in the S13 is epoxy resin-polyurethane-Silicate cement, and the mass ratio of epoxy resin, polyurethane and Silicate cement is 1:1:2-3.

6. The method for preparing a thermal insulation and sound insulation mortar according to claim 3, characterized in that: The preparation method of the polymer damping material comprises the following steps: S21, adding methyl vinyl silicone rubber into an internal mixer, adding modified mica flakes three times, and mixing until the modified mica flakes are completely mixed into the methyl vinyl silicone rubber; S22, re-refining until the modified mica sheet and the methyl vinyl silicone rubber are uniformly mixed, and then leaving at room temperature for 1 week to obtain a silicone rubber mixture; S23, putting the silicone rubber mixture into an open mill and mixing it until it is completely rolled, adding a vulcanizing agent at room temperature and passing it thinly on the open mill, and removing it after mixing evenly to obtain a mixed rubber; S24, the mixed rubber is put into a mold, vulcanized and formed on a flat vulcanizer, and granulated to obtain a granular polymer damping material.

7. The method for preparing a thermal insulation and sound insulation mortar according to claim 6, characterized in that: The preparation method of the modified mica sheet comprises the following steps: S31, adding a silane coupling agent dropwise into a mixed liquid of deionized water and anhydrous ethanol to react to obtain a modified liquid; S32, placing the nano-mica sheet in an oven and baking it to obtain an active mica sheet; S33, adding active mica flakes and stearic acid to the modified liquid, adjusting the pH to 4-5 with acetic acid, stirring and dispersing the mixture evenly, and reacting the mixture at room temperature; S34. After the reaction is completed, the reaction liquid is placed in an oven for drying to obtain a modified mica sheet.

8. The method for preparing a thermal insulation and sound insulation mortar according to claim 6, characterized in that: The mass ratio of methyl vinyl silicone rubber to modified mica sheet in S21 is 99.2-99.7:0.3-0.8, the mixing temperature is 60-70°C, the mixing interval is 5 minutes, and the single mixing time is 10-15 minutes. The back-mixing temperature in S22 is 70-75°C, and the back-mixing time is 10-20 minutes. The vulcanizing agent in S23 is any one of benzoyl peroxide, 2,4-dichlorobenzoyl peroxide, and diisopropylbenzene peroxide.

9. The method for preparing a thermal insulation and sound insulation mortar according to claim 7, characterized in that: The silane coupling agent in S31 is any one of KH-550, KH-560, and KH-570, the mass ratio of the silane coupling agent, deionized water, and anhydrous ethanol is 1:1:18-25, and the reaction is carried out at room temperature for 30-40 minutes. The oven temperature in S32 is set to 100-120°C, and the baking time is 1-2 hours. The ratio of the active mica flakes, stearic acid, and modified liquid in S33 is 1-2:2-4:50, the stirring speed is 1000-2000rpm, the stirring time is 30-40 minutes, and the reaction is carried out at room temperature for 2-4 hours after the stirring is completed. The oven temperature in S34 is set to 120-130°C, and the baking time is 2-3 hours.

10. The method for preparing a thermal insulation and sound insulation mortar according to claim 3, characterized in that: The stirring speed of the stirrer in S1 is set to 80-130 rpm, and the stirring time is 3-5 min. The slow stirring in S2 is 80-130 rpm, and the stirring time is 2-3 min. The fast stirring is 150-200 rpm, and the stirring time is 2-3 min.

Citation Information

Patent Citations

  • Phase-change and energy-storage mortar of ternary composite paraffin / glazed hollow beads and preparation method of phase-change and energy-storage mortar

    CN104446238A

  • High-damping high-temperature silicon sulfide rubber and preparation method and application thereof

    CN105778519A

  • Thermal-insulation and sound-insulation mortar and preparation method thereof

    CN108484215A

  • Impact-resistant heat-preservation and sound-insulation light building block

    CN108840638A

  • Special dry-mixed mortar for plastering construction via 2D guniting method

    CN112551994A